GAMIFICATION STRATEGIES IN HIGHER EDUCATION: LEVERAGING PAST IN THE ERA OF PANDEMIC (Proceedings of the International Conference on Education, 2021)
The on-going pandemic has shifted how education, teaching strategies, and technology interact with each other. With the universities forced by the COVID-19 to cease on-campus education and immigrate to virtual class settings, virtual tools, once perceived as a supporting or supplementary education aspect, evolve to be the center stone of contemporary education. While vast arrays of rearrangements are taking place and new ways of class delivery styles are experimenting, the need for providing an engaging online content delivery strategy still exists. As a result, to support a dynamic teaching structure and achieve desired learning outcomes, some university and college lecturers start to employ non-traditional teaching techniques. One of the most widely used and relatively controversial techniques that emerged as a solution is gamification. Whether this teaching method is effective or not has not been well established. It is also still questionable how this strategy can be utilized in a virtual learning environment. Motivated to contribute this on-going debate, the present paper proposes to conduct a systematic literature review following the “Preferred Reporting Items for Systematic Reviews and Meta-Analyses” (PRISMA) methodology to answer the following set of questions: (1) Is gamification a viable teaching strategy? (2) What are the commonly used gamification strategies? (3) Can gamification-based teaching be incorporated to online classes? This study utilizes the Web of Science (WoS) Core Collection database to mine data for the last five years to answer research questions. The results indicate that gamification is an effective teaching strategy and can be easily integrated into virtual class settings. Findings contribute to the relevant literature strand while providing insight about contemporary teaching styles to lecturers.
Keywords: gamification; PRISMA; educational innovation; higher educatio; COVID-19